Aplikasi Pemesanan Undangan Digital Berbasis Android - Dian Pratiwi, Resky; Hasnawati, Hasnawati (Jurnal Sintaks Logika, 2024)
Technological developments are revolutionizing digital invitations from printed paper to digital forms that offer greater efficiency and convenience. The aim of this research is to build an Android-based digital invitation ordering system so that it can help the process between customers and owners. The method used for this Android application is a quantitative method with the help of the Android Studio application with the help of the HTML programming language which was carried out for two months at a printing shop in the city of Parepare. The results of this research can make it easier for buyers to carry out the digital invitation ordering process more easily and save time.